(untitled) (Agroindustrial Science, 2025)
This study evaluated the effects of adding microencapsulated ferrous sulfate (MFS) and ferric pyrophosphate (FPP) to a fresh cheese product. Five treatments were manufactured: a control (CTRL) and cheeses fortified with MFS or FPP at 90 mg Fe/kg (MFS1, FPP1) and 300 mg Fe/kg (MFS2, FPP2). The physicochemical characteristics (dry matter, moisture, mineral content, and color) and sensory profiles were analyzed. Results indicated that fortification decreased moisture content and increased dry matter. The MFS2 treatment showed the highest iron content (225.05 mg/kg) without compromising calcium levels. Significant color changes were observed only in the a* (redness) component of the FPP2 treatment. Sensory analysis revealed that the CTRL and FPP2 treatments were most liked, while the MFS2 treatment was least liked due to a pronounced metallic and rancid flavor. In conclusion, the type and concentration of the iron compound significantly influenced the cheese’s final characteristics, whereas storage time had a minimal effect. FPP is a more suitable fortificant than MFS for maintaining the sensory quality of fresh cheese.